THE APPLICATION OF ARTIFICIAL NEURAL NETWORKS TO LANDSLIDE SUSCEPTIBILITY MAPPING AT JANGHUNG, KOREA - Lee S.; Ryu J.; Lee M.; Won J. (My University, 2006)
The purpose of this study was to develop techniques for landslide susceptibility using artificial neural networks and then to apply these to the selected study area at Janghung in Korea. Landslide locations were identified from interpretation of satellite images and field survey data, and a spatial database of the topography, soil, forest, and land use. Thirteen landslide-related factors were extracted from the spatial database. These factors were then used with an artificial neural network to analyze landslide susceptibility. Each factor's weight was determined by the back-propagation training method. Five different training sets were applied to analyze and verify the effect of training. Then the landslide susceptibility indices were calculated using the back-propagation weights, and susceptibility maps were constructed from Geographic Information System (GIS) data for the five cases. Landslide locations were used to verify results of the landslide susceptibility maps and to compare them. The artificial neural network proved to be an effective tool for analyzing landslide susceptibility.
Keywords: BACKPROPAGATION; TRAINING SITE; WEIGHT; GIS; SPATIAL DATABASE